Impacts of agricultural management practices on soybean and corn crops evident in groundtruth data and thematic mapper vegetation indices - Thenkabail, Prasad S.; Ward, A.D.; Lyon, J. (American Society of Agricultural and Biological Engineers, 1994)
Vegetation indices from Landsat-5 Thematic Mapper (TM) observations on single dates in August 1988, a drought year, and August 1989, a year with wet early season conditions, were used to study the impact of agricultural management and cultural practices on soybean (Glycine max) and corn (Zea mays) crop growth and yield. Management and cultural practices studied included date of planting, tillage, soil association, drainage, plant density, and stress factors. Crop ground-truth information consisted of leaf area index, wet biomass, dry biomass, and grain yield. During both years ground-truth data were collected from at least 50 commercial farms every one to three weeks. Multispectral TM vegetation indices were developed using the mid-infrared bands 5 and 7 as well as the commonly used near-infrared and red bands. Two mid-infrared vegetation indices proved to be particularly useful in identifying management practice impacts on both crops. For crops, yield and crop growth measurements gave similar trends versus TM vegetation indices. Planting date, plant density, an index of crop stress, and tillage significantly impacted on soybean and corn crop attributes.